On a Hybrid Genetic Algorithm for Solving the Container Loading Problem with no Orientation Constraints - Hasni, Hamadi; Sabri, Houssem (Journal of mathematical modelling and algorithms, 2013)
This paper presents a new hybrid genetic algorithm for solving the container loading problem in the general case, precisely when the boxes have no orientation constraints. In order to improve the genetic algorithm efficiency, we developed a hybrid method, based on deterministic approaches combining the wall-building, level-slice approach and strip packing. A serie of experiments was achieved on 47 related benchmarks from the OR-Library. We could reach an average utilization of 94.47% and an average computation time of 840s on a 1.7 GHz core duo.